2017
DOI: 10.1177/1591019917706052
|View full text |Cite
|
Sign up to set email alerts
|

Curative and adjunctive AVM Onyx embolization of AVMs through the choroidal arteries

Abstract: Objective The anterior or posterior choroidal artery is often recruited to supply deep location arteriovenous malformations (AVMs). This study is to report curative and adjunctive AVM Onyx embolization through these arteries. Methods This study retrospectively reviewed six patients with cerebral AVMs who underwent endovascular embolization through the choroidal arteries between October 2015 and October 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Good outcomes can be achieved with AVM embolization. For instance, in 2017, Lv et al performed 4 AVM embolizations through the AChA; among these cases, 3 AVMs achieved curative embolization, and fourth case was a pre-surgical adjunctive procedure 70 .…”
Section: Arteriovenous Malformationsmentioning
confidence: 99%
“…Good outcomes can be achieved with AVM embolization. For instance, in 2017, Lv et al performed 4 AVM embolizations through the AChA; among these cases, 3 AVMs achieved curative embolization, and fourth case was a pre-surgical adjunctive procedure 70 .…”
Section: Arteriovenous Malformationsmentioning
confidence: 99%
“…[7,24] From a literature review of AVMs with embolization through the PChoA, Ezura et al reported the first safe embolization case of thalamic AVM through the PChoA as adjunctive embolization followed by GKS in 1992; [5] however, only a few reports of AVMs embolized through PChoA have been reported. [2,5,9,14,26,27] The location of AVMs embolized from PChoA included the ventricle, splenium, thalamus, and temporal lobe. [4,14,26] In addition, Onyx and NBCA were the main embolic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection, radiotherapy, and endovascular treatment are available therapeutic methods for AVM [18]. Embolization with the microcatheter performed as a curative procedure through the MPChA should be taken with the main aim to secure the weak structures [18,19]. existence of ventricular microaneurysms in the choroidal arteries [23].…”
Section: Discussionmentioning
confidence: 99%